Giant Popliteal Synovial Cyst Associated with Rheumatoid Arthritis - Duman, Evrim; Acar, Ahmet; Yağız Atlı, Osman; Çevik, Hüseyin Bilgehan (Cerrahpaşa Medical Journal, 2022)
Popliteal synovial cyst is an enlarged bursa, which communicates with the knee joint and is frequently encountered in daily orthopedic practice, is unlikely to be seen as a space-occupying lesion throughout the entire extremity. The main complaints of the patient were pain, limited range of motion of the knee, and a swelling behind the leg. On magnetic resonance imaging, a cystic lesion with 471 cm3 volume was detected in the popliteal region in the posterior of the gastrocnemius, with lobulated contours and containing extensive synovial pannus from mid-thigh to mid-calf. Total excision of the cyst was performed, and the connection between the cyst and the knee joint was tied and pursed. We present a case of giant popliteal synovial cyst that was the largest popliteal synovial cyst associated with rheumatoid arthritis, which impaired the patient’s quality of daily life with limitation of knee range of motion. Popliteal synovial cyst excision with the posterior approach and blockage of the connection between the cyst and the knee joint may provide satisfactory clinical results. Cite this article as: Duman E, Acar A, Atlı OY, Çevik HB. Giant popliteal synovial cyst associated with rheumatoid arthritis. Cerrahpaşa Med J. 2022;46(2):172-174.